2019
DOI: 10.5606/tgkdc.dergisi.2019.15143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain scoring and free cortisol levels of postoperative analgesic methods in cardiac surgery: A new perspective

Abstract: Bu çalışmada kalp cerrahisi yapılması planlanan hastalarda komplikasyonları önlemek amacıyla cerrahi sonrası ağrıyı en aza indirgeyen en uygun analjezik yöntem değerlendirildi. Ça lış ma pla nı: Ocak 2016-Haziran 2016 tarihleri arasında Amerikan Anesteziyoloji Derneği Fiziksel Durum Sınıf III ve ejeksiyon fraksiyonu %50 üzerinde olup elektif koroner arter baypas greftleme yapılan toplam 60 hasta (27 erkek, 33 kadın; ort. yaş 63 yıl; dağılım, 49-77 yıl) çalışmaya alındı. Hastalar yoğun bakım ünitesine kabulleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The current study reveals increased serum cortisol at one week in the participants with better pain control. This finding aligns with a study conducted by Özmen et al, who reported lower free serum cortisol levels in patients who achieved better pain control after cardiac surgery [ 29 ]. In contrast to stress hormones, the level of D-dimer was found to be comparable in both groups.…”
Section: Discussionsupporting
confidence: 92%
“…The current study reveals increased serum cortisol at one week in the participants with better pain control. This finding aligns with a study conducted by Özmen et al, who reported lower free serum cortisol levels in patients who achieved better pain control after cardiac surgery [ 29 ]. In contrast to stress hormones, the level of D-dimer was found to be comparable in both groups.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the study of Özmen et al (21) showed that there were no statistically significant differences between the groups in terms of the length of hospital stay with a (p-value of >0.05).…”
Section: Discussionmentioning
confidence: 92%
“…In the afternoon, the elevated cortisol levels returned earlier to the initial values. In another study, Özmen et al (25) compared the cortisol levels in postoperative analgesia using the local anesthetics (Bupivacaine) and the central opiate administration (Fentanyl). Results were more favourable for the local anesthetics, the patients had lower cortisol levels and reported less postoperative pain than with the centrally administered opiates.…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%